EVALUASI VALIDITAS ISI DAN KONSTRUK LEMBAR KERJA PESERTA DIDIK (LKPD) TERMOKIMIA BERBASIS INKUIRI TERBIMBING - Rahmawati, D H (rc-institut, 2019)
This study has developed a guided inquiry-based student worksheet on thermochemical material and determined the validity of constructs and constructs of the LKPD. this type of research is research and development (R & D). the instrument used is a validation sheet. the data from the validation sheet were analyzed by cohen cappa formula. the average kappa moment of the five validators in the content validity was 0.86 with a very high level of validity and the average kappa moment of the five validators in the content validity was 0.87 with a very high validity level. the results of the data show that LKPD is valid in terms of component contents and construct components.